The silent baroque - Als, Hilton; Bowman, John; Cameron, Dan; Cottingham, Laura; Croak, James; Eckart, Christian; Graham, Dan; Greenfield Sanders, Timothy; Hajamadi, Fariba; Halley, Peter; Hart, Claudia; Joseph, Regina; et al. (Salzburg : Galerie Thaddaeus Ropac, 1989)
Bickerton, Ashley ; Bleckner, Ross ; Bowman, John ; Cemin, Saint Clair ; Croak, James ; Eckart, Christian ; Eckhart, Christian ; Graham, Dan ; Guerrilla Girls ; Hajamadi, Fariba ; Halley, Peter ; Hsu, Tishan ; Koons, Jeff ; Lasker, Jonathan ; Lemieux, Annette ; McDermott & McGough ; Mullican, Matt ; Otterson, Joel ; Richter, Gerhard ; Robbins, David ; Rockman, Alexis ; Schuyff, Peter ; Steinbach, Haim ; Steir, Pat ; Stephan, Gary ; Sturtevant, Elaine ; Taaffe, Philip ; Vaisman, Meyer ; Warhol, Andy ; Wool, Christopher ; Zalopany, Michele ; Zwack, Michael
The silent baroque, Galerie Thaddaeus Ropac, Salzburg, 30 May - 30 August 1989
Engels
boek